2017
DOI: 10.1038/s41559-016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of mother–infant interactions in a diverse range of mammal species

Abstract: Left-cradling bias is a distinctive feature of maternal behaviour in humans and great apes, but its evolutionary origin remains unknown. In 11 species of marine and terrestrial mammal, we demonstrate consistent patterns of lateralization in mother-infant interactions, indicating right hemisphere dominance for social processing. In providing clear evidence that lateralized positioning is beneficial in mother-infant interactions, our results illustrate a significant impact of lateralization on individual fitness. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 29 publications
6
79
3
Order By: Relevance
“…It is unlikely, however, that this can explain the difference in results between the behaviours. The previous study of lateralized social behaviour has found the results of analyses based on multiple and single observations to be consistent in a wide range of mammal species studied (Karenina et al, 2017). In addition, in the majority of observations, the direction of trunk movements was the same in two subsequent trunk-to-genitals contacts performed by the same male.…”
Section: Animal Behaviourmentioning
confidence: 60%
See 2 more Smart Citations
“…It is unlikely, however, that this can explain the difference in results between the behaviours. The previous study of lateralized social behaviour has found the results of analyses based on multiple and single observations to be consistent in a wide range of mammal species studied (Karenina et al, 2017). In addition, in the majority of observations, the direction of trunk movements was the same in two subsequent trunk-to-genitals contacts performed by the same male.…”
Section: Animal Behaviourmentioning
confidence: 60%
“…This type of analysis does not allow estimation of individual preferences, but is often used to assess the one-sided behavioural biases at the population level (Bourne and Todd, 2004;Siniscalchi et al, 2012;Karenina et al, 2017). The first observation of lateral trunk use from each individual was included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the right hemisphere's control of social responding, pigeons display more rapid social reactions to members of the flock on their left side, processed by the right hemisphere [12]. Also, as shown in a wide range of vertebrate species, infants are positioned more commonly on their mother's left side [13], thus being monitored by her right hemisphere. The right hemisphere also comes into play when the animal is under stress, and in these circumstances it has a dominant role in controlling responses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among vertebrates, 61 species (out of 119 measured) show population-level limb preferences, of which 25 species are mammals, 30 birds, and 6 amphibians, reptiles, and fish [4]. Some other animal species also have behavioural hand biases up to 90% at the species level [5][6][7][8], and many other species have individually stable hand preferences [9,10]. However, within our evolutionary clade, humans are the only great ape that shows strong, species-universal biases towards one direction of handedness.…”
Section: Introductionmentioning
confidence: 99%